Role of Frontline Demonstration in Boosting the Pulse Production - Pathak, Jagannath; Singh, Ajeet; Singh, Bhupendra; Mishra, Rahul (Indian Journal of Extension Education, 2011)
Pulses have been traditionally recognized as an indispensable constituent of Indian diet. The great good that pulses have done to the people of this country is by their ideally supplementing the cereal rich diet of predominantly vegetarian masses by virtue of their being rich in protein and several essential amino-acids. The ease with which they fit into the crop rotation and crop mixtures, their long recognized property of restoration of soil fertility. Productivity of pulses at farmers’ field is very low as compare to research plots. It may be due to several biotic and abiotic factors. But the main reason behind this is that, technological gaps in adoptions of pulse production technologies and other factors also. In such situation FLDs can play a vital role in boosting of pulse production because FLDs conducted at farmers field under the close supervision of kvk scientist. Keeping in view the importance of FLDs, the kvk Burhanpur conducted front line demonstrations on newly released varieties of Urd and Gram at farmers’ fields with full package of practices. Results revealed that higher yield was obtained in each year in both Urd and Gram crop and higher B: C ratio supported that demonstrated technology is for better than the farmers practice.